The Rural Free University and the Cooperative Extension Service - Jim Killacky (Educational Considerations, 1986)
The Cooperative Extension Service (CES) has been an acknowledged leader in rural adult education. As rural economies shift, however, many of the services offered through CES agents seem inappropriate. This paper explores the rural free university model and its usefulness in linking CES resources with local needs.